Need Analysis for Developing a Natural Science Learning Website with the Theme of Biotechnology in Improving Digital Literacy - Liska Berlian; Annisa Novianti Taufik; Ilvi Triyani (Jurnal Penelitian Pendidikan IPA, 2023)
The development of technological rapidly changes the learning process more broadly. Demands for students or prospective science teachers to improve their digital literacy skills with the help of website-based media are needed in the learning process so that it can take place optimally. The development of biotechnology has also developed rapidly in the last few years, thus demanding that students or prospective science teachers be more responsive to information and be able to present this information interactively. Unfortunately, many students or prospective science teachers are not able to understand biotechnology because it is considered that the concept of biotechnology is difficult to understand. For this reason, it is necessary to have a needs analysis to find out the aspects needed and develop the learning and learning resources needed to improve digital literacy skills and understand the concept of biotechnology. The aim of this study is to analyze the needs of learning media based on a biotechnology theme website that would be developed, so that it can improve the digital literacy skills of students or prospective science teachers. The needs analysis was carried out as a preliminary study on Borg & Gall's research and development methods, which are included in the research and information collecting stage. The analysis of the needs for developing learning tools includes student analysis, concept analysis, task analysis, and learning objectives analysis. This needs analysis is accompanied by a literature review and observation results. The results obtained are a thorough and real needs analysis on the development of a biotechnology theme website to improve the digital literacy abilities of science teacher candidates, which can be applied at the next research and development stage